Michigan statistical abstract. - Michigan. State University of Agriculture and Applied Science, East Lansing; Bureau of Business and Economic Research (East Lansing [s.n.], 1955)
Annual, 1977- Biennial, 1958-1976
Keywords: Michigan -- Statistics